2021
DOI: 10.3390/su13094616
|View full text |Cite
|
Sign up to set email alerts
|

Urban Strategies Enabling Industrial and Urban Symbiosis: The Case of Slovenia

Abstract: Industrial symbiosis (IS) recognizes the exchange of waste resources and by-products between companies that do not normally cooperate in resource exchange; on the other hand, urban symbiosis (UrS) recognizes the use of solid waste in cities as input sources for industries that do not normally accept these sources. It is difficult to realize both in a pre-planned process, and there are few successful initiatives based on the exchange of waste and energy. The main objective of this research is to find out whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Neves et al [61] observed that developing countries such as India, Bangladesh and Egypt are new entrants in the tradition of synergy practices. Resultantly, their scholastic contributions based on case studies are modest as compared to industrialized/developed economies [62]. The late start of industrial activities, as well as the lack of capacity and awareness regarding contextual potential are considered to be major hindrances for smart industrial production in newly industrializing regions [19].…”
Section: Discussionmentioning
confidence: 99%
“…Neves et al [61] observed that developing countries such as India, Bangladesh and Egypt are new entrants in the tradition of synergy practices. Resultantly, their scholastic contributions based on case studies are modest as compared to industrialized/developed economies [62]. The late start of industrial activities, as well as the lack of capacity and awareness regarding contextual potential are considered to be major hindrances for smart industrial production in newly industrializing regions [19].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the industrial transfer between China and the countries along the "Belt and Road" has improved the integration, interaction, and coordination among industries, thereby promoting the improvement of reciprocal and symbiotic industry relations. Models ( 4)- (6) show the regression results with the inclusion of control variables, and the results also indicate that industrial transfer has a significant positive effect on the integration, interaction, and coordination between bilateral industries.…”
Section: Benchmark Regressionmentioning
confidence: 94%
“…Water supply: sewerage, waste management and remediation activities Analysis of documents, networks, projects, national programs and national statistical sources [169] Professional, scientific, and technical activities 7…”
Section: Transportation and Storagementioning
confidence: 99%
“…In Singapore, Kerdlap et al [83], in a food waste valorization network, assessed the life-cycle environmental impacts of seeking to convert food waste into valuable resources through the M3-IS-LCA methodology, which was designed to perform a process-based life-cycle assessment of any IS scenario. Momirski et al [169] conducted research with the objective of finding out if there are strategies in the selected companies for waste exchange that support the emergence, existence, and development of IS in Slovenia, identifying the fact that in this country, IS processes are in the early stages, with a slower development than expected.…”
Section: Waste Integrationmentioning
confidence: 99%